EFEKTIVITAS NATION BRANDING “WONDERFUL INDONESIA” SEBAGAI SEBUAH STRATEGI DALAM HUBUNGAN DIPLOMASI PEMERINTAH INDONESIA TAHUN 2011-2018 - Triesanto Romulo Simanjuntak (Universitas Kristen Satya Wacana, 2019)
Tourism is an important aspect for Indonesia. Indonesia's condition is very supportive for the sustainability of tourism. Tourism contributes to development in various fields of life, especially in the economic sector. Moreover, Indonesia has the opportunity to promote its tourism maximally under the auspices of the ATF (ASEAN Travel Forum), as a forum for promoting tourism in ASEAN. Wonderful Indonesia is present as a form of national branding for Indonesian tourism internationally. The presence of Wonderful Indonesia is a form of public diplomacy, namely to promote the nation's image. In its implementation, public diplomacy does not only rely on the role of the government, but also the roles of other actors, such as the community, individuals and non-governmental organizations to play a role in it. This paper uses qualitative research and focuses on the use of Wonderful Indonesia as Indonesia's national branding. In the process, there are three aspects that become the focus of Indonesia's national branding, namely: historical, cultural, and social. The historical aspect pays attention to the dynamics of Indonesian tourism, from the signing of various MoUs, when losing international trust due to the human rights case and reforms in 1998, to finally having the courage to manage tourism independently in 2015-2019. Cultural aspects pay attention to Wonderful Indonesia as a representation of the wealth of traditional values. Finally, the social aspect that examines domestic and international promotion as a form of frame for self-image and Indonesia's reputation in the world.